Improved Direct Routing Approach for Mobile IP Systems - Alshahrani, Ali (International Journal of Interactive Mobile Technologies (iJIM), 2019)
The mobile IP communication protocol is a flexible system for mobile connection that is designed to allow the device to be moved between networks while maintaining a permanent IP address. IP datagrams using mobile IP can be routed to a specific mobile station (MS) regardless of its current internet location. However, to facilitate such routable characteristics, the communication with an MS that is visiting a foreign network is intermediate with communication between the home agent (HA) and the foreign agent (FA) which increase the total delay and harms the communication performance, especially when the MS continuously moves from a network to another. Accordingly, to handle the delay issue, this paper proposes a new approach for mobile IP direct routing, based on the “follow-me” principle. The proposed approach depends on sending a new temporary care-of-address (CoA) for the previously visited network as the MS moves to another to keep a reliable tracking–like process with the HA. Accordingly, the agents of all the visited networks play the same principles as the HA role whenever the MS moves from a network to another. The proposed approach influences the delay and the speed of the delivery of internet packets. The simulation showed that the proposed method decreases the delay by up to 50% compared to the direct routing approach.